PERBEDAAN TINGKAT KELELAHAN MATA PADA MAHASISWA DENGAN GANGGUAN REFRAKSI DAN TANPA GANGGUAN REFRAKSI - Pebrianti, Kadek Tari; Permatananda, Pande Ayu Naya Kasih; Sunariasih, Ni Nyoman (E-Jurnal Medika Udayana; Vol 12 No 2 (2023): E-Jurnal Medika Udayana, 2023)
Eye fatigue or asthenopia are symptoms that arise due to excessive use of the visual system that is in an imperfect condition to obtain visual acuity. Refractive error is one of the individual elements that affects eye fatigue. People with asthenopia have an accommodating reaction to refractive error. Eye fatigue is a condition that needs to be addressed because it can have a negative impact on a patient's quality of life. The purpose of this study was to determine the difference in the level of eye fatigue in medical students with refractive errors and without refractive errors at the Faculty of Medicine and Health Sciences, Warmadewa University. This research is an analytic observational study with a case control research design. Sampling was carried out in a  total sampling with a total sample of 114 people, with total sample of 57 people in each case and control group. Data were obtained by measuring photostress recovery test (PSRT), checking visual acuity and consist of questionnaire. The results of the study on the subject of eye fatigue showed low eye fatigue level of 26.4%, moderate eye fatigue level of 40.4% and severe eye fatigue level of 35.1%. The results of the bivariate analysis using chi square test showed that there was a relationship between refractive errors and eye fatigue (p value = 0.000) and there were differences in the level of eye fatigue in students with and without refractive errors (p value = 0.01).